(3LQGFe GdGYJOGA Ydi GdehXa GdYGe (B: s (3GdMeGjI GdehVhYjI ddehXa GdYGe (B/ s - (3ESdGe Wg TgHhs; (3eOMJ YHOGdMdje QeVGf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3jYO ehVhY GdehXajf GdYehejjf ef Cge GdehVhYGJ GdJj JTZd Ohd GdYGde aj GdYUQ GdNOjK QZe GNJdGa GdGJLGgGJ GdSjGSjI h GdGbJUGOjI h GdGLJeGYjI (B. (3EP dG JSJWjY OhdI Cf JDOj QSGdJgG EdG ef NdGdge HGYJHGQge YUH GdOhdI h COGJgG GdefaPI h OYGeJgG GdbhjI h GdeYHQjf Yf fgVJgG (B: (3adG jJUhQ hLhO OhdI MOjKI Ohf Cf jchf dOjgG ehXahf h eOjQhf jfhHhf YfgG deeGQSI hXGFagG h SdWGJgG GdeNJUIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2012s
(3HHdjhLQGajG(B: (3UaMGJ (B381-391s
Keywords: (3GdbGfhf GdLfGFjs; (3GdEYJOGAGJs; (3GdehXahf GdYehejhf s; (3MeGjI GdhXjaIs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs